Estrogens as immunotoxicants: 17α-ethinylestradiol exposure retards thymus development in zebrafish (Danio rerio) - Kernen, Larissa; Phan, Audrey; Bo, Jun; Herzog, Elio L.; Huynh, John; Segner, Helmut; Baumann, Lisa (Aquatic toxicology, 2022)
Estrogenic endocrine disrupting compounds (EEDCs) can cause alterations in sexual development and reproductive function of fish. Growing evidence suggests that EEDCs can also interfere with development and function of innate immunity of fish. The present study examined a potential disruptive effect of EEDCs at field-relevant concentrations on the development of adaptive immunity, more specifically the thymus. Zebrafish (Danio rerio) were exposed from fertilization until 64 days post-fertilization (dpf) to environmentally relevant (3 and 10 ng/L) concentrations of the synthetic estrogen 17α-ethinylestradiol (EE2). The exposure duration covered the period of initial thymus differentiation to maximum growth. Thymus development was assessed by histological and morphometric (thymus area) analysis, thymocyte number, and transcript levels of thymocyte marker genes. Additionally, transcript levels of the estrogen receptors (esr1 and esr2a) were determined. The EE2 exposure altered sexual development (gonad differentiation, transcript levels of hepatic vitellogenin and estrogen receptors) of zebrafish, as expected. At the same time, the EE2 treatment reduced the thymus growth (thymus area, thymocyte number) and transcript levels of thymus marker genes. The expression of the thymic estrogen receptors responded to the EE2 exposure but in a different pattern than the hepatic estrogen receptors. After the 64-day-exposure period, the juvenile fish were transferred into clean water for another 95 days to assess the reversibility of EE2-induced effects. The thymic alterations were found to be reversible in female zebrafish but persisted in males. The present study provides the first evidence that the development of the fish adaptive immune system is sensitive to EEDCs, and that this takes place at concentrations similar to those that disrupt sexual development.
Gesehen am 24.05.2022
Available online 12 November 2021